DESIGNING STOP MOTION VIDEO USING LEARNING STYLE APPROACH TO TEACH VOCABULARY AT 4TH GRADE SD MUHAMMADIYAH PURWODININGRATAN II IN THE ACADEMIC YEAR 2015/2016 - M. Luthfi Imama; Rahmi Munfangati (UAD TEFL International Conference)
This research was proposed to design Stop Motion video using learning style approach as a media to teach vocabulary for 4th grade students of SD Muhammadiyah Purwodiningratan II in the academic year 2015/2016.ADDIE (Analyze, Designing, Developing, Implementation, and Evaluating) was used by the researcher as a research methodology. The data for needs and learning style analysis was collected by giving questionnaire, doing an interviews and doing observation in the classroom. In order to develop the Stop Motion video, the prototype of the product was evaluated by the expert. Then, the video was implemented on the learning process to know its feasibility. In order to measure the effectiveness of the Stop Motion video, pre-test and post-test were given to class 4.A.1 as an experiment class and class 4.A.2 as a control class. The data of the pre-test and post-test were calculated by using SPSS 16.00. After the implementation, the researcher conducted an evaluation by analyzing the response of the student to the media. The result of the research suggested that stop motion video suitable to teach 4 grade elementary students of SD Muhammadiyah Purwodiningratan II.